Design and Test of Combined Air Suction Cotton Breed Seeder - Yudao Li; Zhanhua Song; Fade Li; Yinfa Yan; Fuyang Tian; Xuezhen Sun (Journal of Engineering)
In view of such a phenomenon that nowadays cotton breeding and seeding mainly depend on artificial planting in China, a kind of combined air suction cotton breed seeder was designed, which is mainly composed of combined air suction seed metering device, three-way switch device, waste seed recovery device, vacuum fan, and so on. It can sow two rows at a time, and the line spacing, plant spacing, and sowing depth can be continuously adjusted to achieve precise sowing. The model of “suck before and blow after” is adopted in seed clearing, which makes seed clearing both clean and rapid. The force, speed, and acceleration of cotton seed are theoretically analyzed when the seed metering device is filled with seeds and then determines the main structural parameters and motion parameters of the device. This paper takes Lumianyan No. 37 as the research object, adopts the single-factor test and the quadratic regression rotation orthogonal test, selects the forward speed, air pressure, and groove plate width of the air suction cup as the experimental factors, and conducts an experiment of the seeder’s performance, by analyzing the influence law of the seeder’s velocity on its seeding variation coefficient. This paper concludes that the coefficient of variation is small when the velocity is 1.2–1.5 m/s and finds the optimal range of unit velocity when sowing and finally builds the mathematical models including multiples index and missing index. After parameter optimization, this paper makes the optimal parameters for sure; that is, the seeder’s velocity ranges from 1.3 to 1.5 m/s, wind pressure ranges from 2.5 to 2.8 kPa, and the width of the air suction groove ranges from 2.6 to 2.8 mm. At this time, the multiples index and missing index of the combined air suction cotton breed seeder are less than 3%, whose sum total is less than 5%. In the field test, the seed clearing performance of the seed clearing system is tested, and the seed clearing rate has reached 100%, meeting the seeding requirements in cotton tablets.